From studying translation to working in translation: mind the gap - Chumbo, Isabel (2018)
There will always be good translators and there will always be a need for good translators. This commonplace statement has been challenged by the development of the markets, as a result of globalization of trade and technologies, outsourcing and flexibility. A TAUS (Translation Automation User Society) report from 2014 stated that there is a 250 million dollars industry waiting for translators. These are still many times viewed as non-professional people who know a language or two and can use dictionaries or google to translate. In fact, professions in multilingual communication have developed fast over the last two decades and the profile of the “translator” is much more complex, involving translators, interpreters, revisers, editors, subtitlers, localizers, terminologists, technical writers, product engineers and project managers. This revolution seems to demand for new skills. Where can they be obtained? In most European countries primary training of translators is developed in Higher Education Institutions. The European Union Association of Translation Companies met in Lisbon this year and explicitly reported the existence of a gap between the industry and the translation graduates. This leads us to believe that universities and polytechnics have to change their approaches in translator training and more synergies should be created. This presentation will propose a set of changes which may be able to reduce the gap between academic training and the demands of the labour market. Traineeships and internships for students and trainers are just one example of a good contribution for the employability of graduates who, more than ever, have to possess a vast set of skills and keep a high quality standard in their performance if they want to be job-ready.